Protective effects of hydrocolloid nanoemulsion coatings against myofibrillar protein oxidation in frozen trout - Kara, Ayşe; Çağlak, Emre; Karslı, Barış (Frontiers in Nutrition, 2025)
In this study, rainbow trout filets were coated using a dipping method with a nanoemulsion derived from aloe vera gel (AVG) and hemp seed oil (HSO; 5% HSO and 3% AVG). The filets coated with the nanoemulsion were then subjected to slow (−20 °C) and fast freezing (−40 °C) temperatures. The experimental groups were formed as follows: 20C (filets coated with pure water and frozen at −20 °C), 20N (filets coated with nanoemulsion and frozen at −20 °C), 40C (filets coated with pure water and frozen at −40 °C), and 40N (filets coated with nanoemulsion and frozen at −40 °C). Physicochemical analyses [pH, sulfhydryl groups (-SH), disulfide bonds (S-S), carbonyl content, myofibril fragmentation index, water-holding capacity, drip loss, TVB-N, and TBA] were performed monthly over a 6-month storage period. The results of this study indicated that none of the experimental groups exceeded the reported limit values for pH, TVB-N, and TBA during the 6-month storage period. It was observed that the filets coated with nanoemulsion and subjected to fast freezing (40N) delayed protein oxidation, as evidenced by the lower values of sulfhydryl groups, disulfide bonds, carbonyl content, and myofibril fragmentation index. Additionally, these filets maintained acceptable levels of quality parameters such as TVB-N, TBA, and pH, preserving their edibility. In conclusion, nanoemulsions containing AVG and HSO were found to improve the quality of fish products, helping them stay fresh for a longer period.